Effects of supercritical fluid-extracted Hibiscus cannabinus L. seed oil on colon cancer in vitro and in vivo - Abd Ghafar, Siti Aisyah (2013)
Kenaf (Hibiscus cannabinus) from the family Malvaceae, is a valuable fiber plant native to India and Africa, and is currently planted as the fourth commercial crop in Malaysia. Kenaf seed oil contains alpha-linolenic acid, phytosterol such as β-sitosterol, vitamin E and other antioxidants with chemopreventive properties. The present study evaluated cytotoxicity towards human colorectal cancer cell line (HT29) and cancer chemopreventive properties of kenaf seed oil from supercritical carbon dioxide fluid extraction (KSO-SFE). Kenaf seed oil was extracted via supercritical carbon dioxide fluid (SFE) at 9 different permutations of parameters based on range of pressure (200-600 bars) and temperature (40-80°C): 200/40, 200/60, 200/80, 400/40, 400/60, 400/80,600/40, 600/60 and 600/80. All the nine KSO-SFE were screened for cytotoxicity towards human colorectal cancer cell line (HT29) and mouse embryonic fibroblast cell line (NIH/3T3) using MTS assay. KSO-SFE of 600/40 showed the strongest cytotoxicity towards HT29 with IC50 of 200 μg/ml. Nevertheless, IC50 for NIH/3T3 was not detected even at the highest concentration of KSO-SFE employed. Cell cycle analysis exhibited a significant increase in the number of KSO-SFE-treated cells at sub- G1 phase, indicating the induction of apoptosis by the extract. The induction of apoptosis was further confirmed by Annexin V/PI and AO/PI staining. For the chemopreventive properties of KSO-SFE, 60 male Sprague Dawley rats were randomly assigned to 6 groups. All groups were induced with azoxymethane (AOM) except for the negative control (Group 1). They were 1) negative control group, 2) positive control group (without any treatment), 3) vehicle control group (administered with emulsifier (Tween 80), 4) group treated with 500 mg/kg body weight KSO-SFE; 5) group treated with 1000 mg/kg body weight KSO-SFE and 6) group treated with 1500 mg/kg body weight KSO-SFE. The animals were injected subcutaneously once a week for 2 weeks with 15 mg/kg body weight of AOM at 7 weeks of age. Rats were euthanized after 90 days of the experiment. There was no significant difference in weight gain among the groups. Number of aberrant crypt foci (ACF) ranged from 84.4 ± 4.43 to 179.5 ± 12.78 in Group 2, 3, 4, 5 and 6. ACF were reduced by 45.3%, 51.4% and 53.1% in rats fed with 500, 1000 and 1500 mg/kg body weight of KSO-SFE, respectively, compared to the positive control group (p<0.05). For ACF multiplicity, ACF with 4, 5 or more crypts were significantly lower (p<0.05) in rats fed with KSO-SFE compared to the positive control group. The findings indicate that KSO-SFE reduced AOM–induced ACF in Sprague Dawley male rats. The effects of KSO-SFE on fifteen genes involved in colon carcinogenesis were analyzed on AOM-induced rats using GenomeLabGeXP genetic system. It shows that treatment with KSO-SFE increased the expression of tumor suppressor genes (APC and p53), reduced the expression of tumor marker genes (COX-2and β-catenin) and did not change the expression of large tumor suppressor and TNF receptor genes compared to the positive control group (p<0.05). KSO-SFE has also shown to activate the apoptotic pathway by up regulating the expression of caspases (caspase 9, caspase 2 and caspase 3) and pro-apoptotic genes (bax and bad), and down regulating the expression of anti-apoptotic gene (bcl-2). Treatment with KSO-SFE also affects the cell cycle genes with increased expression of cell cycle inhibitor (p21, cip1) and decreased expression of cyclin D1. Assessment of toxicity of KSO-SFE at 500, 1000 and 1500 mg/kg body weight/day towards Sprague Dawley rats was also performed. The parameters for toxicity include body and organ weight, haematology,clinical chemistry, pathology and expression of toxicity-related genes. No mortality or treatment-related adverse effects were observed at all doses throughout the period of 90 days. All the parameters were in normal range. Low creatinine level at all doses and low total cholesterol level at 1000 and 1500 mg/kg body weight of KSO-SFE were noted but insignificant. Further analysis using GenomeLabGeXP genetic system on the liver tissues showed the expression of genes involved in xenobiotic metabolism, DNA damage, cell cycle arrest and apoptosis was at normal level. In short, The No Observed Adverse Effect Level (NOAEL) for KSO-SFE at 1500 mg/kg body weight/day. In conclusion, data from this study demonstrate the potential of KSO-SFE as a chemopreventive agent against colon cancer.